Synthesis of new hydroxy-2-styrylchromones - Santos, Clementina M.M. (2003)
http://apps.isiknowledge.com/full_record.do?product=UA&search_mode=GeneralSearch&qid=5&SID=V1M67gPH3IpI7j5a98j&page=1&doc=1&colname=WOS